Psychological Factors Influencing Job Satisfaction Among Korean Long-Term Care Hospitals Nurses - Jun Min Sim, Youngju Jee (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Aim: This study aimed to investigate job satisfaction of nurses in long-term care hospitals and examine the factors affecting it. Design: A cross-sectional study at three long-term care hospitals. Methods: Data were collected from 135 voluntary nurses recruited from 3 long-term care hospitals. The survey questions measured job satisfaction, role conflict, communication competence, resilience, and general characteristics. Data were analyzed using descriptive statistics, independent t-test, one-way Pearson correlation coefficient and standard multiple regression with Statistical Package for the Social Sciences 18.0 for Windows. Results: The factors influencing job satisfaction of subjects were the presence of standard instruction for nursing practice and resilience, which explained 12.3% of variance in job satisfaction of them.